Circularly Polarized Spin‐Selectivity Absorbing Coding Phase Gradient Metasurface for RCS Reduction. Issue 3 (27th January 2020) - Feng, Maochang; Chen, Xiaoli; Li, Yongfeng; Zheng, Qiqi; Han, Yajuan; Zhang, Jieqiu; Wang, Jiafu; Hou, Yi; Liu, Zhewei; Li, Xuojian; Wang, Chao; Jing, Jao; et al.
Abstract: A novel spin‐selectivity absorbing coding phase gradient metasurface (SACPGM) is proposed and demonstrated. The coding element consists of spin‐selectivity absorbing unit cells, which exhibit different absorption characteristics for left‐handed circularly polarized and right‐handed circularly polarized incidence wave due to their spin‐selectivity absorbing properties. The scattering patterns of the SACPGM can be synthetically manipulated by the reflection of the spin‐selectivity absorbing unit cells, the phase gradient of the coding elements, and the coding sequences. As an example, a two‐bit SACPGM with random coding sequence is designed to reduce radar cross section (RCS) by a combination of absorption, beam deflection, surface wave coupling, and diffusion scattering. Both simulated and measured results agree well and demonstrate that the SACPGMs possess excellent performance for RCS reduction. This strategy can help realize stealth applications under bi‐static detections. Abstract : A novel spin‐selectivity absorbing coding phase gradient metasurface (SACPGM) is proposed and demonstrated. As an example, a two‐bit SACPGM with random coding sequence is designed to reduce radar cross section by a combination of absorption, beam deflection, surface wave coupling, and diffusion scattering. The strategy can help realize stealth applications under bi‐static detections.